SHAKESPEARE'S INFLUENCE ON CONTEMPORARY LITERATURE: - Sheeraz Ahmad Naik; Vikas Farooq (CV. RADJA PUBLIKA, 2024)
William Shakespeare, the bard of Avon, has had an unparalleled influence on literature, language, and the arts for over four centuries. This research paper delves into the profound impact of Shakespeare's work on contemporary literature. By examining various facets such as themes, character archetypes, language, and adaptation, this paper aims to elucidate how Shakespeare's legacy continues to shape modern storytelling and literary practices.